Philosophy Education as a Means of Developing Student Soft Skills - Wira Yustika Rukman; Samuel Urath; Hegar Harini; Abu Muna Almaududi Ausat; Suherlan Suherlan (Edumaspul: Jurnal Pendidikan, 2023)
Higher education is one of the important stages in preparing students to enter the world of work. In addition to demanding high academic abilities, the world of work also expects graduates to have qualified soft skills. The purpose of this study is to analyse philosophy education as a means of developing students' soft skills. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results showed that innovative and creative philosophy teaching can motivate students, while students' needs and interests need to be considered in teaching. Lecturers have an important role in guiding and facilitating discussions and debates in class, so that students can develop critical thinking skills, good argumentation, public speaking, empathy, and cooperation.